The role of Saudi universities in facing some contemporary challenges from the point of view of faculty members in colleges of education - Aloqayli, Alya Ali (Journal of Educational and Psychological Sciences, 2025)
The study aimed to: Knowing the reality of the role of Saudi universities in facing ethical challenges, Identify their role in facing social challenges, as well as doctrinal challenges from the point of view of faculty members in colleges of education, in addition to developing proposed mechanisms to activate the role of Saudi universities in facing contemporary challenges, The study used the survey descriptive curriculum, The questionnaire is a study tool, distributed to a sample of 100 faculty members at Imam Mohammed bin Saud Islamic University, King Saud University, Shaqra University, The study came up with the most important results: There is a clear deficiency in the role of Saudi universities to face contemporary challenges, as the most deficient axes were: The social challenge with the lowest average (1.61 out of 3.00), Then the nodal challenge (atheistic) averaging (1.65), The study provided proposed mechanisms to activate the role of Saudi universities to face these contemporary challenges, including: The need for universities to activate their social responsibilities, Developing a national index to measure the extent to which universities apply this responsibility, Establishing a social responsibility department that is directly linked to the university director, The study also recommended organizing seminars and various activities to address these challenges.